Investigating Teacher Use of Practice Tests for Formative Purposes - Sarah M. Bonner (The Evaluation Center at Western Michigan University, 2009)
This paper describes an intensive professional development program focused on supporting teachers at high-need urban high schools in use of practice tests for formative assessment purposes. Teachers engaged in professional development while offering intensive summer school to students with histories of failure on state tests in science and mathematics. Specific skills that teachers developed included item analysis of practice tests, planning around assessment results, and providing feedback to students. The study used a quasi-experimental pretest/posttest design with an intervention and a comparison group, analysis of classroom artifacts, follow-up surveys, and long- term follow-up with teachers. Students in the summer programs experienced large gains in performance, and teachers reported more frequent and varied use of tests for formative purposes, even one-and-one-half years after the end of training. This material is based upon work supported by the National Science Foundation's Math and Science Partnership program under Grant No. 0412413